Utilização do ciclo PDCA para redução de desperdícios de produtos congelados em uma indústria alimentícia - Reis, Igor Afonso dos (2021)
The reduction of waste in manufacturing has been a topic that has been increasingly studied by industry professionals and is fundamental in taking over large and small companies. To seek this optimization and reduce waste, process improvements must be sought throughout its production chain, with no intention of reducing losses, increasing profits, and ensuring greater market protection. This work aims to analyze and apply the PDCA method (Plan, Do, Check and Act) in meet processors, focusing on reducing product waste and recovery hours in a frozen food supervision IQF (Individually Quick Frozen). The main results, we highlight the identification of the root causes that increased the waste of products, the proposal and implementation of improvement and standardization actions, such as which resulted in the average reduction of two machine stoppages to none in the three months of implementation analyzed . As each stop generated a loss of approximately 500 kg of products, with a project application or a reduction to zero waste during and after application.